2014
DOI: 10.4238/2014.august.28.20
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of H-FABP and ACSL4 gene polymorphisms and their associations with intramuscular fat content and backfat thickness in different pig populations

Abstract: ABSTRACT. Here, we analyzed the distribution of H-FABP/ (HinfI, MspI, and HaeIII) and ACSL4/RsaI polymorphisms, and the associations of these 4 polymorphic loci with intramuscular fat (IMF) content and backfat thickness (BFT) RsaI polymorphisms were absent in Yanan and Jinhua pigs. Linkage disequilibrium analysis indicated that the 3 loci (HinfI, MspI, and HaeIII) were separated. Association analysis showed that the H-FABP/HinfI locus significantly affected IMF content in DLY (P < 0.05) and Yanan (P < 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Recent studies have shown that HFABP is related to adipogenesis in 3T3-L1 preadipocytes of the fat Banna mini-pig inbred line51. The distribution of HFABP and ACSL4 gene polymorphisms has been associated with IMF content and back fat thickness in different pig populations52. The expression of HFABP in TP-DSP was 1.78-fold higher than that in YY-LL, suggesting that it is related to the higher lipid deposition ability of TP and DSP pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that HFABP is related to adipogenesis in 3T3-L1 preadipocytes of the fat Banna mini-pig inbred line51. The distribution of HFABP and ACSL4 gene polymorphisms has been associated with IMF content and back fat thickness in different pig populations52. The expression of HFABP in TP-DSP was 1.78-fold higher than that in YY-LL, suggesting that it is related to the higher lipid deposition ability of TP and DSP pig breeds.…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al . ). Significant up‐regulation of H‐FABP gene indicates the development and maturity of the adipose tissue (Li et al .…”
Section: Discussionmentioning
confidence: 97%
“…Gondim (2015) also reported that SNPg.240T>C when homozygous for the T allele decreases the first period of coverage, and the delivery/ parturition interval, showing that the result of the population studied in this experiment reached the apex for selection. Chen et al (2014) analyzed the H-FABP polymorphisms using PCR-RFLP using 3 restriction enzymes in six swine breeds and as the results of this study found a high predominance of one allele in at least 50% of the analyzed loci. Li et al (2006), when studying which would be the best markers for native Chinese breeds that would help in selection and conservation, showed significant differences in the frequencies of genotypes and alleles between breeds.…”
Section: Discussionmentioning
confidence: 99%